2019
DOI: 10.2147/oajc.s226481
|View full text |Cite
|
Sign up to set email alerts
|

<p>Are Women In Lomé Getting Their Desired Methods Of Contraception? Understanding Provider Bias From Restrictions To Choice</p>

Abstract: BackgroundDespite improvements in contraception availability, women face persistent barriers that compromise reproductive autonomy and informed choice. Provider bias is one way in which access to contraception can be restricted within clinical encounters and has been established as common in sub-Saharan Africa. This analysis assessed the prevalence of provider restrictions and the potential impact on women’s method uptake in Lomé, Togo.MethodsThis sub-analysis used survey data from provider and client intervie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…There is limited evidence from Togo on the factors in uencing contraceptive uptake and use which can be used to inform family planning programs. Among the few family planning related studies conducted in Togo, the majority examined male engagement and the need to address misconceptions surrounding modern methods and the risks of advanced maternal age and high parity pregnancy through appropriate channels such as facility, community and home based counseling in order to increase contraceptive use (4,(21)(22)(23). Evidence from facility-based surveys in Togo found high levels of provider restrictions for family planning related to partner consent, age, and marital status but did not nd an effect on whether clients were able to obtain their preferred methods as a result (21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is limited evidence from Togo on the factors in uencing contraceptive uptake and use which can be used to inform family planning programs. Among the few family planning related studies conducted in Togo, the majority examined male engagement and the need to address misconceptions surrounding modern methods and the risks of advanced maternal age and high parity pregnancy through appropriate channels such as facility, community and home based counseling in order to increase contraceptive use (4,(21)(22)(23). Evidence from facility-based surveys in Togo found high levels of provider restrictions for family planning related to partner consent, age, and marital status but did not nd an effect on whether clients were able to obtain their preferred methods as a result (21).…”
Section: Introductionmentioning
confidence: 99%
“…Among the few family planning related studies conducted in Togo, the majority examined male engagement and the need to address misconceptions surrounding modern methods and the risks of advanced maternal age and high parity pregnancy through appropriate channels such as facility, community and home based counseling in order to increase contraceptive use (4,(21)(22)(23). Evidence from facility-based surveys in Togo found high levels of provider restrictions for family planning related to partner consent, age, and marital status but did not nd an effect on whether clients were able to obtain their preferred methods as a result (21). Strategies aimed at improving the quality of post abortion care by increasing providers knowledge, attitudes and skills and reducing unnecessary restrictive biases were found effective in increasing access to contraception (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…In another analysis utilizing this same dataset, the authors found that though provider restrictions were widespread, they did not affect women's ability to receive the method they wanted among women who had a desired method prior to their FP consultation. 38 Though there could be different explanations for this finding, the one that seems most plausible is that a woman's demand for a specific method overrides the provider's restrictions. Potentially, women who arrive at the clinic with a desired method in mind are able to negotiate receipt of this method, even in cases where the provider reported a restriction.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, most provider-imposed restrictions are related to age and marital status. [38][39][40] We hypothesized that provider training would be associated with LARC uptake, since other studies in SSA have found providers to be a barrier based on biases based on sociodemographics, misconceptions about safety or lack of training in provision. 41 However, we did not find a significant association between provider training and LARC uptake, which could be due to several reasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation